Robust Network Inhibition and Decay of Early-Phase LTP in the Hippocampal CA1 Subfield of the Amazon Rodent Proechimys - Reyes-Garcia, Selvin Z.; de Almeida, Antônio-Carlos Guimarães; Ortiz-Villatoro, Nancy N.; Scorza, Fulvio A.; Cavalheiro, Esper A.; Scorza, Carla A. (Frontiers in Neural Circuits, 2018)
Background: Diverse forms of LTP have been described, but one of the most investigated is encountered in the glutamatergic synapses of the hippocampal cornu Ammonis (CA1) subfield. However, little is known about synaptic plasticity in wildlife populations. Laboratory animals are extremely inbred populations that have been disconnected from their natural environment and so their essential ecological aspects are entirely absent. Proechimys are small rodents from Brazil´s Amazon rainforest and their nervous systems have evolved to carry out specific tasks of their unique ecological environment. It has also been shown that long-term memory duration did not persist for 24-h in Proechimys, in contrast to Wistar rats, when both animal species were assessed by the plus-maze discrimination avoidance task and object recognition test. Methods: In this work, different protocols, such as theta burst, single tetanic burst or multiple trains of high frequency stimulation, were used to induce LTP in hippocampal brain slices of Proechimys and Wistar rats. Results: A protocol-independent fast decay of early-phase LTP at glutamatergic synapses of the CA1 subfield was encountered in Proechimys. Long-term depression and baseline paired-pulse facilitation were investigated but no differences were found between animal species. Input/output relationships suggested lower excitability in Proechimys in comparison to Wistar rats. Bath application of D-AP5 and CNQX prevented the induction of LTP in both Proechimys and Wistar. However, in marked contrast to Wistar rats, LTP induction was not facilitated by the GABAA antagonist in the Amazon rodents, even higher concentrations failed to facilitate LTP in Proechimys. Next, the effects of GABAA inhibition on spontaneous activity as well as evoked field potentials were evaluated in CA1 pyramidal cells. Likewise, much lower activity was detected in Proechimys brain slices in comparison to those of the Wistar rats. Conclusions: These findings suggest a possible high inhibitory tone in the CA1 network mediated by GABAA receptors in the Amazon rodents. Currently, neuroscience research still seeks to reveal molecular pathways that control learning and memory processes, Proechimys may prove useful in identifying such mechanisms in complement to traditional animal models.